Socialnopravna vročica slovenskega zakonodajalca - Mišič, Luka (Javna uprava, 2021)
The author critically analyses recently proposed or enacted amendments to Slovenian social law and the manner of their passing. He looks closely at the amendment to the Slovenian Market Regulation Act and Labour Relations Act, the proposed Debureaucratisation Act and the missing amendment to the Cross-border Provision of Services Act. The first amendment, which introduced favourable treatment of Slovenian-resident frontier workers in cases of unemployment, is contrary to EU law and the provisions on equal treatment. The second amendment, which introduced new grounds of dismissal for older workers, who fulfilled old-age retirement criteria, is contrary to international law and the provisions on equal treatment. The proposed Debureaucratisation Act systematically unfounded and contrary to the principle of vertical solidarity is to introduce a limited social security base (the so called social cap), whilst the Cross-border Provision of Services Act still awaits to be amended. It was supposed to be amended almost a year ago due to the transposition of Directive (EU) 2018/957 into the Slovenian legal order. The recent activities of the Slovenian lawmaker, both the Government and the Parliament, reveal a special interest- -based approach to law-making, questioning both a systematically compliant as well as a long-term development, not a decay of Slovenian social law.
Keywords: delovno pravo; enaka obravnava; equal treatment; EU law; frontier workers; labour law; obmejni delavci; older workers; pravo EU; social security; social security contributions; socialna varnost; starejši delavci; vertical solidarity